PENGARUH KEPEMILIKAN INSTITUSIONAL, SUSTAINABILITY REPORT DAN INTELLECTUAL CAPITAL TERHADAP NILAI PERUSAHAAN - Mutyyara Ermanda; Dwi Fitri Puspa (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2022)
The purpose of this study is to empirically examine the effect of institutional ownership, sustainability report and intellectual capital on firm value. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019. The sample selection was based on the purposive sampling method and finally 105 companies that met the criteria and the number of observations were 525 observations. The analytical technique used in this research is Multiple Linear Regression with Eviews application tools. The results show that institutional ownership has a negative and significant effect, intellectual capital has a significant effect on firm value and the sustainability report has no effect on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019. This research provides empirical evidence that intellectual capital is information used as a reference by investors in assessing companies. The wider disclosure of intellectual capital is able to increase investor confidence so that stock prices increase.